KEPEMIMPINAN TRANSFORMASIONAL DAN KULTURAL - Shidqiyah Shidqiyah; Dedi Eko Riyadi HS; Zahratun Naemah (AHSANA MEDIA: Jurnal Pemikiran, Pendidikan dan Penelitian Ke-Islaman, 2021)
Leadership is the existence of a process in leadership to exert social influence on others, so that the other person carries out a process as desired by the leader. Whatever is the impetus to increase the motivation of both leaders and subordinates is always done. The motivation and spirit are imprinted to always make changes for the better. Changes continue to be made by following the development of various times. Various opportunities are taken seriously for more maximal change. An important awareness is instilled that each individual has potential. This type of research is a type of qualitative research with a type of literature study or commonly referred to as library research. A literature study is a study that seeks the main source of information or main data from the literature or from books, journals that are relevant to the research to be carried out.